2010
DOI: 10.1037/a0019221
|View full text |Cite
|
Sign up to set email alerts
|

Recognition by familiarity is preserved in Parkinson's without dementia and Lewy-Body disease.

Abstract: Objective:The retrieval deficit hypothesis states that the lack of deficit in recognition often observed in patients with Parkinson's disease is because of the low retrieval requirements of the task, given that these patients have retrieval and not encoding deficits. To test this hypothesis we investigated recognition memory by familiarity in Parkinson's patients and in patients with Lewy Bodies disease and Parkinson with dementia. Method: We analyzed to what extent the experimental groups were able to recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 54 publications
5
27
1
8
Order By: Relevance
“…Some studies support the idea of a deficit in F but not in R (Davidson et al, 2006;Weiermann et al, 2010); others confirm the existence of a deficit in R (Edelstyn et al, 2007;Edelstyn et al, 2010;Hay et al, 2002); finally, the results of our previous study (Algarabel et al, 2010) demonstrated the ability of PD patients to use perceptual F. Considering the previous state of affairs, the aim of the present study was to determine whether PD patients show deficits in R but not in F when both are based on conceptual grounds (see, for example, Lanska, Olds, & Westerman, 2014). We estimated R directly by using an associative recognition paradigm that it is typically considered to involve only R when applied with the appropriate parameters (Wixted et al, 2010).…”
Section: The Present Studysupporting
confidence: 72%
See 3 more Smart Citations
“…Some studies support the idea of a deficit in F but not in R (Davidson et al, 2006;Weiermann et al, 2010); others confirm the existence of a deficit in R (Edelstyn et al, 2007;Edelstyn et al, 2010;Hay et al, 2002); finally, the results of our previous study (Algarabel et al, 2010) demonstrated the ability of PD patients to use perceptual F. Considering the previous state of affairs, the aim of the present study was to determine whether PD patients show deficits in R but not in F when both are based on conceptual grounds (see, for example, Lanska, Olds, & Westerman, 2014). We estimated R directly by using an associative recognition paradigm that it is typically considered to involve only R when applied with the appropriate parameters (Wixted et al, 2010).…”
Section: The Present Studysupporting
confidence: 72%
“…Results indicated that patients with early PD, advanced PD, and dementia with Lewy bodies used F to improve recognition to a similar extent as control groups. Unlike these groups, PD patients with dementia were not able to benefit from F (Algarabel et al, 2010). However, some of the groups that exhibited similar F scores had lower general recognition scores.…”
Section: Recollection and Familiarity In Pdmentioning
confidence: 86%
See 2 more Smart Citations
“…These studies have usually found that recollection is impaired, but that familiarity is preserved in mild to moderate nondementing PD (Algarabel, et al, 2010;Edelstyn et al, 2007;Edelstyn et al, 2010;Hay, Moscovitch, & Levine, 2002;Rodr Iguez, Algarabel, & Escudero, 2014;Shepherd et al, 2013). However, familiarity has sometimes been found to be impaired as previously indicated (Davidson, et al, 2006;Weiermann, et al, 2010).…”
Section: Q6mentioning
confidence: 98%